Teologia litúrgica de Ione Buyst - Fonseca, Joaquim (Revista Eclesiástica Brasileira, 2024)
No ensejo da comemoração dos 60 anos da promulgação da “Constituição para a Sagrada Liturgia Sacrosanctum Concilium” e da recém-publicada “Carta apostólica Desiderio Desideravi sobre a formação litúrgica do povo de Deus” do Papa Francisco, o texto apresenta alguns apontamentos sobre a vida e a obra da conceituada teóloga liturgista Ione Buyst. Desde sua chegada ao Brasil, em 1964, ela tem-se dedicado à teologia e à pastoral litúrgica. O presente estudo consta de duas partes: a primeira se ocupa de uma breve biografia de Ione Buyst; a segunda, de sua teologia litúrgica. Aqui, em grandes linhas, serão destacadas a importância dessa teóloga liturgista em sua incansável busca por uma ciência litúrgica para o Brasil e América Latina. Nessa abordagem, serão tecidas algumas considerações relacionadas ao âmbito metodológico desenvolvido por ela, ou seja, a implementação de uma ciência litúrgica que se apreende a partir da experiência/vivência ritual. Abstract: In view of the celebration of the 60th anniversary of the “Constitution for the Sacred Liturgy Sacrosanctum Concilium” and the recently published “Apostolic Letter Desiderio Desideravi on the liturgical formation of the people of God”, by Pope Francis, the text presents some notes on the life and work of the renowned liturgical theologian Ione Buyst. Since her arrival in Brazil in 1964, she has dedicated herself to theology and liturgical pastoral care. This study consists of two parts: the first will deal with a brief biography of Ione Buyst; the second, intends to offer considerations about her liturgical theology. In broad terms, the importance of this liturgical theologian in her tireless search for a liturgical science for Brazil and Latin America will be highlighted. In this approach, some considerations will be made related to the methodological scope developed by her, i.e., the implementation of a liturgical science that is learned from ritual experience. Keywords: Ione Buyst; Liturgy; Liturgical science; Rituality; Mystagogy; Liturgical laboratory; Ritual Music.